2020
DOI: 10.1530/ec-19-0543
|View full text |Cite
|
Sign up to set email alerts
|

Impact of hyperthyroidism on cardiac hypertrophy

Abstract: The cardiac growth process (hypertrophy) is a crucial phenomenon conserved across a wide array of species and is critically involved in the maintenance of cardiac homeostasis. This process enables an organism to adapt to changes in systemic demand and occurs due to a plethora of responses, depending on the type of signal or stimuli received. The growth of cardiac muscle cells in response to environmental conditions depends on the type, strength and duration of stimuli, and results in adaptive physiological res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 122 publications
(140 reference statements)
0
17
0
Order By: Relevance
“…In spite of their wide effects on metabolism, the use of THs for therapeutic purposes remains controversial because, as mentioned, these hormones may induce other non-metabolic effects. In more detail, like hyperthyroidism, treatment with exogenous THs can induce thyrotoxicosis, a condition characterized by a variety of adverse symptoms, such weight loss, osteoporosis, atrial fibrillation, embolic events, and increased risk of heart failure [33,34,181].…”
Section: The 35-diodothyronine (35-t2) As a Hormonementioning
confidence: 99%
See 1 more Smart Citation
“…In spite of their wide effects on metabolism, the use of THs for therapeutic purposes remains controversial because, as mentioned, these hormones may induce other non-metabolic effects. In more detail, like hyperthyroidism, treatment with exogenous THs can induce thyrotoxicosis, a condition characterized by a variety of adverse symptoms, such weight loss, osteoporosis, atrial fibrillation, embolic events, and increased risk of heart failure [33,34,181].…”
Section: The 35-diodothyronine (35-t2) As a Hormonementioning
confidence: 99%
“…Given their action on metabolism, it seemed, in the past, that they could be used as pharmacological agents for the treatment of obesity. However, this approach could be not applied, due to adverse side effects on many organs and systems and, in particular, on the cardiovascular system and the heart's rhythm [33,34]. Yet, in recent years, it has been found that some metabolites of thyroid hormones, and especially 3,5-diiodo-L-thyronine (3,5-T2), are endowed with interesting metabolic activities that may be of clinical interest as possible therapeutic options in the treatment of overeating disorders [20].…”
Section: Introductionmentioning
confidence: 99%
“…D3, with substrate affinity T4>T3 and function for T3 degradation, is similar in activity to D1_2 and found in the central nervous system. From its localization at the plasma membrane D3 may migrate to the nuclear membrane in ischemia, where it inactivates T4 and T3 ( 26 ).…”
Section: Blood Transport Metabolisation Cellular Uptake and Cellular Effects Of Thmentioning
confidence: 99%
“…The cardiac renin–angiotensin–aldosterone system (RAAS) has been reported to be activated in hyperthyroidism and that could escalate cardiac renin function and angiotensin II (Ang II) levels [ 42 ]. Besides, the cardiac angiotensin II receptor type 2 (AT2 receptor) was shown to be upregulated in response to hyperthyroidism, suggesting that there are alterations of key molecules of the major axis of RAAS in hyperthyroidism.…”
Section: Introductionmentioning
confidence: 99%
“…Besides, the cardiac angiotensin II receptor type 2 (AT2 receptor) was shown to be upregulated in response to hyperthyroidism, suggesting that there are alterations of key molecules of the major axis of RAAS in hyperthyroidism. Use of angiotensin-converting enzyme (ACE) or angiotensin II receptor type 1 (AT1 receptor) inhibitory drugs were shown to depreciate RAAS in cardiac cell proliferation due to enhanced thyroid hormone and suggest that RAAS acts a pivotal part in thyroid hormone-mediated cardiac hypertrophy [ 42 ].…”
Section: Introductionmentioning
confidence: 99%